1993
DOI: 10.7164/antibiotics.46.606
|View full text |Cite
|
Sign up to set email alerts
|

TAN-1057 A-D, new antibiotics with potent antibacterial activity against methicillin-resistant Staphylococcus aureus. Taxonomy, fermentation and biological activity.

Abstract: TwoGram-negative bacteria were found to produce the newantibacterial antibiotics TAN-1 057 A, B, C arid D. The producing bacteria were characterized and designated as Flexibacter sp. PK-74 and PK-176.Theseantibiotics wereactive against Gram-negativeand Gram-positivebacteria, including methicillin-resistant Staphylococcus aureus. TAN-1 057 A inhibited protein biosynthesis in Escherichia coli and S. aureus.It showed excellent protective effects against an experimental methicillin-resistant S. aureus infection in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
55
1
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 12 publications
1
55
1
3
Order By: Relevance
“…Within this group, genetic techniques were previously available only for members of the genus Bacteroides and related bacteria in the genera Prevotella (47) and Porphyromonas (13). Cytophagas and flavobacteria are important as pathogens of animals and humans (3,6,8,9,30,31,45), as agents of biodegradation (18,28,38), and as producers of novel antibiotics and antitumor drugs (11,26,35,38). We have recently demonstrated that some of the genetic tools described above function in a number of bacteria belonging to the Cytophaga-Flavobacterium group (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this group, genetic techniques were previously available only for members of the genus Bacteroides and related bacteria in the genera Prevotella (47) and Porphyromonas (13). Cytophagas and flavobacteria are important as pathogens of animals and humans (3,6,8,9,30,31,45), as agents of biodegradation (18,28,38), and as producers of novel antibiotics and antitumor drugs (11,26,35,38). We have recently demonstrated that some of the genetic tools described above function in a number of bacteria belonging to the Cytophaga-Flavobacterium group (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This group of bacteria includes a number of animal and human pathogens (3,6,8,9,30,31,45), bacteria capable of degrading complex biomolecules (18,28,38), and bacteria that produce novel and potentially useful antibiotics and other bioactive compounds (11,26,35,38). Adaptation of the tools described here should allow genetic analyses of many of these bacteria.…”
mentioning
confidence: 99%
“…TAN 1057 displays in vitro (5) and in vivo (9) antibacterial activity against staphylococci, including methicillin-resistant Staphylococcus aureus strains. Its in vitro activity is excellent in synthetic medium and pure fetal calf serum (FCS), whereas in a standard assay medium such as Mueller-Hinton (MH) broth, the MICs increase 10-to 256-fold (e.g., the MICs against S. aureus P209 in AOAC and MH medium are 0.1 and 3.1 g/ml, respectively) (3,12). Preliminary mechanism-of-action studies revealed that TAN 1057 inhibits protein synthesis in whole-cell experiments and in cell-free translation assays (12).…”
mentioning
confidence: 99%
“…Its in vitro activity is excellent in synthetic medium and pure fetal calf serum (FCS), whereas in a standard assay medium such as Mueller-Hinton (MH) broth, the MICs increase 10-to 256-fold (e.g., the MICs against S. aureus P209 in AOAC and MH medium are 0.1 and 3.1 g/ml, respectively) (3,12). Preliminary mechanism-of-action studies revealed that TAN 1057 inhibits protein synthesis in whole-cell experiments and in cell-free translation assays (12). Further experiments demonstrated that the mechanism of action of TAN 1057 is complex.…”
mentioning
confidence: 99%
See 1 more Smart Citation